DOI: 10.1007/978-3-540-85654-2_17
|View full text |Cite
|
Sign up to set email alerts
|

Description Logic to Model a Domain Specific Information Retrieval System

Abstract: In professional environments which are characterized by a domain (Medicine, Law, etc.), information retrieval systems must be able to process precise queries, mostly because of the use of a specific domain terminology, but also because the retrieved information is meant to be part of the professional task (a diagnosis, writing a law text, etc.). In this paper we address the problem of solving domain-specific precise queries. We present an information retrieval model based on description logics to represent ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…We also revealed that non-trivial queries, like those treated in our study, require adding domain knowledge during indexing and querying process. As shown in our previous work, this can be reached using expressive documents and queries languages, respectively during documents and queries content representation [16].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We also revealed that non-trivial queries, like those treated in our study, require adding domain knowledge during indexing and querying process. As shown in our previous work, this can be reached using expressive documents and queries languages, respectively during documents and queries content representation [16].…”
Section: Resultsmentioning
confidence: 95%
“…We notably showed how the use of semantic relationships could provide a precise representation of documents and query content. Relationships can therefore be used during the information retrieval process in order to allow the system to find a relevant document to a given query, even if it does not share any term with that query [16].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…One of the interests in using logic for IR is the fact that the results are predictable and explanatory. For example, Description Logic is explicitly used to formalize knowledge in medical IR systems [13,77]. Belief revision [54] is being investigated to cope with vague queries.…”
Section: Recent Logical Ir Systemsmentioning
confidence: 99%